A revision of Malaxella Ding & Hu (Hemiptera: Delphacidae) with description of a new species - Qin, Dao-Zheng; Zhang, Ya-Lin (Zootaxa, 2009)
The endemic delphacid genus Malaxella Ding & Hu (Hemiptera: Fulgoromorpha: Delphacidae) from China is reviewed and two species, including a new species, M. tetracantha n. sp. (southern China: Hainan) are recognized. The genus and the species are described and illustrated. A key to the species of the genus is also provided.